2000
DOI: 10.1053/euhj.1999.1740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of increased plasma angiotensin II despite ACE inhibitor therapy in patients with congestive heart failure

Abstract: Fifty per cent of patients with heart failure, ha increased plasma angiotension II despite chronic ACE inhibitor therapy. These patients had higher neurohormonal activation and poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(167 citation statements)
references
References 23 publications
5
157
3
2
Order By: Relevance
“…Systemic and tissue Ang II levels are increased in CHF patients (Roig et al 2000) and in CHF rabbits . Ang II enhances CB chemoreceptor activity via the AT 1 receptor (AT 1 R) in the CB (Allen, 1998).…”
Section: Role Of Ang II On Cb Function In Chfmentioning
confidence: 99%
“…Systemic and tissue Ang II levels are increased in CHF patients (Roig et al 2000) and in CHF rabbits . Ang II enhances CB chemoreceptor activity via the AT 1 receptor (AT 1 R) in the CB (Allen, 1998).…”
Section: Role Of Ang II On Cb Function In Chfmentioning
confidence: 99%
“…Angiotensinogen can be converted to angiotensin II by non-renin enzymes, including tissue plasminogen activator (t-PA), cathepsin G, elastase, and chymostatin, while angiotensin I can be converted to angiotensin II by non-ACE enzymes such as chymostatin-sensitive angiotensin II-generating enzyme, chymase, and cathepsin G. 23 Studies have in fact demonstrated "angiotensin II escape," with return of angiotensin II to pretreatment levels, during chronic ACE inhibitor therapy. 15,[29][30][31] Rebound of angiotensin II levels during ACE inhibitor therapy has been correlated with excess mortality in patients with HF. 15 In addition, ACE inhibition is associated with persistent cough in up to 20% of patients, and angioedema in 0.1 to 0.2% of patients.…”
Section: Rationale For Angiotensin II Receptor Blockers In the Managementioning
confidence: 99%
“…15,[29][30][31] Rebound of angiotensin II levels during ACE inhibitor therapy has been correlated with excess mortality in patients with HF. 15 In addition, ACE inhibition is associated with persistent cough in up to 20% of patients, and angioedema in 0.1 to 0.2% of patients. 14 In the Omapatrilat Cardiovascular Treatment vs. Enalapril (OCTAVE) trial, the frequency of angioedema with enalapril was 0.68% (86 of 12,557 patients with hypertension), and was 1.62% in black patients.…”
Section: Rationale For Angiotensin II Receptor Blockers In the Managementioning
confidence: 99%
See 1 more Smart Citation
“…Second, other mediators, such as natriuretic peptides, adrenomedullin and cytokines, induce opposite responses and cause vasodilation and diuretic effects, reduce cellular proliferation and induce apoptosis. High plasma concentrations of some of these mediators, such as norepinephrine and angiotensin, directly contribute to increasing mortality in heart failure, whereas it is believed that other hormones are only indirect markers of greater severity [65,66].…”
Section: Neurohormonal Markersmentioning
confidence: 99%